Cognitive and behavioural outcomes of former preterm children at a tertiary care centre. Issue 8 (3rd August 2018) - Akoury Dirani, Leyla; Sinno, Durriyah; Wheeler, Heidi M.; Tamim, Hani; Charafeddine, Lama
ABSTRACT: There is no current estimation about the impact of prematurity on a child's development in Lebanon. This study describes the developmental profile of 82 former preterm-born children aged between 2 and 8 years. The Wechsler Preschool and Primary Scale of Intelligence, third edition (WPPSI-III) and Achenbach Child Behavior Checklist (CBCL for ages 1½–5 [CBCL/1½–5] or CBCL for ages 6–18 [CBCL/6–18]) results were analysed in a prospective cross-sectional study to evaluate the type and extent of cognitive and behavioural impairments amongst these children. Preterm-born children yielded IQ scores approximately 0.5–1 standard deviation below normative parameters. Significant negative associations were found between WPPSI-III composite scores and specific CBCL scales that suggest a relationship between lower intellectual functioning and more reported behavioural problems. While these findings are limited in generalizability due to the limited sample size, they highlight the need for further assessment of cognitive and behavioural impairments among Lebanese preterm-born children.